Thermal cyclic life of functionally-graded gadolinium zirconate/yitria stabilized zirconia thermal barrier coating - Johari A.D.; Manap A.; Yunus S.M. (ASM International, 2023)
Aluminum alloys; Chromium alloys; Gadolinium; Heat resistance; Heat treatment; Isotherms; Plasma spraying; Thermal fatigue; Yttria stabilized zirconia; Zirconia; Air plasma spray process; Functionally graded; Functionally graded coatings; Gadolinium zirconate; Isothermal heat treatments; Stabilized zirconia; Thermal barrier coating (TBC); Thermal cyclic tests; Thermal barrier coatings